A new interspinous process distraction device BacFuse in the treatment of lumbar spinal stenosis with 5 years follow-up study. Issue 26 (26th June 2020) - Chen, Mengmeng; Tang, Hai; Shan, Jianlin; Chen, Hao; Jia, Pu; Bao, Li; Feng, Fei; Shi, Guan; Wang, Ruideng
Abstract : Abstract: To explore a suitable indication of interspinous process distraction device for lumbar spinal stenosis with BacFuse. Patients of lumbar spinal stenosis (LSS) who experienced interspinous process distraction device surgery with BacFuse from June 2014 to January 2015 in our institute were included. We classified LSS into central and lateral types, and then divided these into severe and moderate according to the degree of stenosis. Each type was divided into 2 groups. Patients in group A underwent distraction without bone decompression (stand-alone), while patients in group B underwent bone decompression combined with distraction. Follow-up was performed at 1 month, 3 months, 6 months, 2 years, and 5 years after surgery. Zurich Claudication Questionnaire (ZCQ) was recorded to assess the patient's postoperative condition at each follow-up. A total of 142 patients were available for follow up at each time interval. There was a significant difference between the preoperative and final follow-up ZCQ scores for every LSS type. In addition, there was no difference between group A and group B in the postoperative ZCQ scores with the exception of the lateral severe type. In the study, 22 of the 23 patients (95.65%) in the lateral moderate type were considered to have a satisfactory result in group B, with a similar result of 93.33% (14/15) in group A ( P  = .75). In the lateral severe type, the patient satisfaction rate was 65.22% (15/23) and 90.63% (29/32) in group A and group B ( P  = .02), respectively. In the central moderate type, the patient satisfaction rate was 81.82% (15/23) and 76.92% (10/13) in group A and group B ( P  = .77), respectively. Satisfaction rate for the follow-up results in the central severe type reached 57.14% (4/7) in group A, and 54.55% (6/11) in group B ( P  = .91). Moreover, no relationship was found between satisfaction and neurogenic intermittent claudication. The most suitable indication for BacFuse treatment was the lateral moderate type. For lateral severe patients, distraction combined with decompression is suggested for a higher satisfaction rate. Severe central spinal stenosis was shown to be a relative contraindication for BacFuse.